Quality Assurance of Service Activities at VNU National Defense and Security Training Center - Nga, Nguyen Thi; Dang, Nguyen Duc (VNU Journal of Science: Education Research; Vol 39 No 1S, 2023)
The study analyze the response level of VNU National Defense and Security Training Center to the learning and living needs of students attending National Defense and Security Education at VNU National Defense and Security Training Center and analyze the factors affecting the service quality of VNU National Defense and Security Training Center through quantitative research methods with a research sample of 400 survey samples from 400 students attending National Defense and Security Education at VNU National Defense and Security Training Center. The research results show that the factors belong to the following areas: attitude, service capacity of staff; infrastructure; implementation process; price/cost; environment has different effects on students' assessment of the service quality of VNU National Defense and Security Training Center.